Inter-Reader Agreement of Multi-Parametric MR Imaging for the Detection of Prostate Cancer: Evaluation of a Scoring System - Quentin, M.; Arsov, C.; Röhlen, S.; Klasen, J.; Antoch, G.; Albers, P.; Blondin, D. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2012)
Purpose: Functional prostate MR is performed in varying combinations of T2-weighted images with diffusion-weighted imaging (DWI), dynamic contrast-enhanced MRI (DCE-MRI), and spectroscopic imaging (MRSI). Recently, a European consensus meeting proposed the use of a simple 5-point scale for estimating the probability of a lesion being malignant. The aim of the present study was to determine the inter-reader agreement of MR imaging using a scoring system based on the recommendations of the consensus. Materials and Methods: The appearance of 108 predefined lesions in three different MR sequences (T2-weighted images, DWI, and DCE-MRI) in 50 functional prostate MR examinations were retrospectively scored by three blinded radiologists using a 5-point scale for each MR sequence. After scoring T2/DWI and T2/DWI/DCE-MRI, every lesion was graded based on its probability for malignancy. The inter-observer reliability was evaluated using Kappa statistics (ĸ). Results: With respect to T2-weighted images, DWI and DCE-MRI ĸ was 0.49, 0.97, and 0.77, respectively. Combined scoring of T2-weighted images and DWI demonstrated correct tumor diagnosis (true positive) in 71 – 88 % (depending on reader) of cases (ĸ = 0.78). The accuracy was further improved to 88 – 96 % after scoring all three MR sequences including DCE-MRI (ĸ = 0.90). Conclusion: The use of a simple 5-point scoring system for T2-weighted images, DWI, and DCE-MRI is feasible in functional prostate MRI and has high inter-observer reliability.
Keywords: prostate; MR imaging; MR diffusion/perfusion; MR functional imaging; decision analysis